Car Rental Application with GPS Tracking for Mileage Detection - Koh, Chia Yin; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2021)
Limited mileage car rental application can be another option for customer to choose renting a car. Car Rental Application with GPS Tracking for Mileage Detection project is proposed to detect the distance travelled by user in mileage. User can book in the mileage they want, while admin will manage the booking request made by user and control the tracking application. Object-Oriented Software Development (OOSD) is used as methodology and developed using Android Studio, Java Programming Language and Firebase. With the three applications, user application that allow user to register, login, make booking request, admin application that allow admin to manage cars, update booking request status, control tracking app, and the tracking application will get the location and detect the mileage travelled. The applications consist of several limitations and suggestion for further improvement in the future are provided.